Monitoring Pembelajaran PAI Berbasis Merdeka Belajar di MAN 2 Palembang - Atika Natasya; Ahmad Zainuri (PAI RAFAH, 2025)
This research aims to monitor and analyze the implementation of Islamic Religious Education learning based on independent learning at MAN 2 Palembang. The main focus of this research is to identify changes that occur in the learning process, analyze the challenges faced and evaluate their impact on learning outcomes and student character development. In achieving these objectives, this research uses a qualitative approach with a case study method. This method was chosen based on the need to obtain an in-depth and comprehensive understanding of the implementation of learning Islamic Education based on independent learning at MAN 2 Palembang. Data collection used direct observation, semi-structured interviews, documentation and FGDs. Data analysis uses a thematic analysis approach. The results showed that the implementation of Islamic Religious Education learning based on independent learning at MAN 2 Palembang has brought positive changes to the learning process and outcomes, increasing student motivation, developing 21st century skills, and strengthening character to be promising results. However, challenges such as teacher readiness, infrastructure, and parental resistance still need to be overcome. The successful implementation of independent learning in the context of Islamic religious education requires a holistic approach involving curriculum development, improving teacher competence, providing adequate infrastructure, and active involvement of all stakeholders. Further research is needed to explore the long-term impact of this approach on students' religious understanding and character building.